Uncertainty Avoidances among International Students towards Malay Food Acceptance - Amira, S. N. (Journal of Education and Vocational Research, 2015)
Uncertainty avoidance towards certain culture and food has dominantly influence the acceptance of food choices among the international students. International students can be describes as a person or group of people who arrives in other country with a priority to pursue their higher tertiary education in a better place. Experiencing new culture, food and people has absolutely influences the level of uncertainty which then resulting the rejection of certain food in the new place. Findings has shown that the uncertainty avoidances of the students has negatively significant (Î²=-.165, p<.01**) with the acceptance of Malay food which than contribute to the ability of the students to accept the Malay food.